Vol. 1760 : Physics of Cancer: Interdisciplinary Problems and Clinical Applications 2016: Proceedings of the International conference, 22-25 March 2016, Tomsk, Russia; AIP Conference Proceedings - Gutmanas E. Y. Elazar Y.; Naimark O. B. Oleg B.; Sharkeev Yu. P. Yury Petrovich (2016, 2016)
Title screen